Diagnostic parameters of Northern blot hybridization technique for detection of citrus viroids in field-grown plants - Umaña Castro, Rodolfo (2017)
Background and Objective: The identification and diagnosis of citrus viroids can be achieved by molecular techniques that directly detect the presence of viroid genomes within infected plant RNA pools. Several studies have reported numerous diagnostic parameters for detection of citrus viroids in field-grown plants. Herein, we report an improved molecular technique based on PAGE-Northern blotting with cDNA DIG-specific (non-radioactive) probes that is rapid, reliable and requires low amounts of tissue from field-grown samples. Materials and Methods: Total RNA was extracted from viroid-infected and negative control bark tissue sampled from field-grown citrus cultivars and subjected to DIG-labeled Northern blot molecular procedures. Results: Based on multi-probe viroid RNA hybridization sensitivity analysis, we were able to detect specific viroids with as little as 8-12 mg of fresh tissue. All cDNA DIG-specific probes yielded strong positive signal only when the specific viroid was present. Signal repeatability observed in 25 membranes was robust, with a total of 84 field samples analyzed. Conclusion: Overall, this molecular diagnostic technique, based on PAGE-Northern blot using cDNA-DIG probes, offered rapid, reliable and robust results, allowing for the direct detection of viroids from minute amounts of bark tissue sampled from field-grown citrus plants.